2013
DOI: 10.1590/s1517-86922013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento com pesos na pressão arterial de repouso em idosas normotensas

Abstract: Introduction: Resistance training (RT) has been widely used for older adults in order to minimize or reverse the deleterious effects of aging in the neuromuscular system. However, the potential benefits of RT on arterial blood pressure and resting heart rate in older adults remain controversial. Objective: To analyze the effect of eight weeks of RT on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and heart rate (HR) in older women without hypertension. Methods: Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…In a recent comprehensive systematic review and meta-analysis of 191 studies assessing HR adaptation following regular physical exercise, Reimers et al [ 70 ] indicated that, in the general population, endurance-based training, as well as combined endurance and strength based-training, significantly decreased the resting HR (2.7 to 5.8 bpm). Specifically, in older adults (>60 years old), previous studies investigating eight-week endurance [ 71 , 72 , 73 , 74 , 75 ] or strength-based [ 76 , 77 , 78 ] training programs (frequency of 1.5 to 3 session/week), showed a beneficial effect for only endurance-based training programs, with a significant reduction of resting HR ranging from 4.5 to 8 beat/min. Regarding the effect of combined endurance and strength training programs on the resting HR of older adults, previous studies have reported a beneficial effect (reduction of 2.4 to 6.1 beat/min) from 12 to 25 weeks of training (frequency of 2 to 3 session/week) [ 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 98%
“…In a recent comprehensive systematic review and meta-analysis of 191 studies assessing HR adaptation following regular physical exercise, Reimers et al [ 70 ] indicated that, in the general population, endurance-based training, as well as combined endurance and strength based-training, significantly decreased the resting HR (2.7 to 5.8 bpm). Specifically, in older adults (>60 years old), previous studies investigating eight-week endurance [ 71 , 72 , 73 , 74 , 75 ] or strength-based [ 76 , 77 , 78 ] training programs (frequency of 1.5 to 3 session/week), showed a beneficial effect for only endurance-based training programs, with a significant reduction of resting HR ranging from 4.5 to 8 beat/min. Regarding the effect of combined endurance and strength training programs on the resting HR of older adults, previous studies have reported a beneficial effect (reduction of 2.4 to 6.1 beat/min) from 12 to 25 weeks of training (frequency of 2 to 3 session/week) [ 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 98%
“…Of the 29 remaining studies, 23 were excluded because they presented inadequate or non-existent information on randomization or because they presented outcomes that did not meet the specific objectives of this study (Figure 1). Thus, six studies were included in this review [26][27][28][29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…The sample size in each study ranged from 17 to 40 participants. In three studies the participants were of both genders 26,27,29 while the others used only female subjects 28,30,31 . The duration of the intervention ranged from eight to 24 weeks, with a frequency of three sessions per week.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations